Design methodology of an online greek language course - Zaphiris, Panayiotis; Zacharia, Giorgos (My University, 2001)
We present a participatory design methodology for developing an online corrunurtity supported Modem Greek language course. The students of the classes collaborate in transcribing real audio lessons, publish and peer review shared notes. Participatory design was implemented as a four step process (a) Building bridges with the intended users (b) Map user needs and suggestions to the system (c) Develop a prototype (d) Integrate feedback and continue the iteration.
Keywords: Distance learning; Online Communities; Participatory Design